Literature Study: the Relationship Between Workload and Work Stress in Nurses - Lubis, Fatma Sri Ramadhan; Maimunah, Putri; Munthe, Supriati; Salianto, Salianto (PROMOTOR, 2024)
Workload is one of the main factors affecting work stress. Workload that is not managed properly can cause significant work stress, with an impact on nurses. Nurses as providers of nursing care, in carrying out their profession often experience stress related to their work. Based on this background description, the author is interested in conducting research in the form of a literature review that aims to analyze the relationship between workload and nurses' work stress. This study used the literature review method where researchers traced several journals with contents and discussions in accordance with the research objectives. This study uses the literature review method where researchers trace several journals with the contents and discussions in accordance with the research objectives. From the results of several journal studies, there is a relationship between workload and work stress.